Bisphosphonates in the Treatment of Patients With Metastatic Breast, Lung, and Prostate Cancer: A Meta-Analysis. Issue 46 (November 2015) - Liu, Jing; Huang, Wenhui; Zhou, Ruoyu; Jia, Shuting; Tang, Wenru; Luo, Ying; Zhang, Jihong
Abstract : Abstract: The purpose of this meta-analysis was to investigate whether bisphosphonates are a key therapy for bone metastases in lung cancer, breast cancer, and prostate cancer by comparing all randomized controlled trials that appraised the effects of bisphosphonates on risk of skeletal-related events (SREs). PubMed, Embase, and Medline databases (up to December 2014) were used to search all related articles. Using the data from 19 available publications, the authors examined the efficacy in treating or reducing the risk of SREs in lung cancer, breast cancer, and prostate cancer by meta-analysis. Bisphosphonates have demonstrated efficacy in treating or reducing the risk of SREs in lung cancer [odds ratio (OR) = 0.81, 95% confidence interval (CI) = 0.69–0.95, P  = 0.008], breast cancer (OR = 0.62, 95% CI = 0.54–0.71, P  = 0.000), and prostate cancer (OR = 0.62, 95% CI = 0.45–0.86, P  = 0.004). This meta-analysis suggests that bisphosphonates have demonstrated efficacy in treating or reducing the risk of SREs in lung cancer, breast cancer, and prostate cancer.